Molecular structure model construction and quantum chemical calculations for weakly caking coal: a case study of Huangling coal in Shaanxi, China - Hongqing Zhu; Rui Li; Binrui Li; Jiashuo Wang; Lintao Hu; Baolin Qu; Linhao Xie; Lei Zhang (Fuel, 2027)

Parent material modulates land use effects on soil organic carbon fractions but not inorganic carbon in subtropical red soils - Rui Jiang; Shuai Liu; Yu Zhang; Enze Xie; Beibei Fan; Fahui Jiang; Samuel Adingo; Lei Gao; Xinhua Peng (Soil and Tillage Research, 2026)

Planarization engineering of benzodithiophene-based nanogrids for enhanced carrier mobility and emission performance - Lei Yang; Jun Yang; Shi-rui Chen; Wen-bin Xie; Cong Sun; Wang-yang Wu; Xin-zhe Peng; Manas Ranjan Dash; Xue-qin Ran; Mohamad Akbar Ali; Ling-hai Xie (Chemical Engineering Journal, 2026)

High-throughput prediction of the lowest triplet excitation energies in organic photovoltaic acceptors using physics-guided excess-factor-corrected fragment descriptors - Lei Cheng; Rui-Cheng Qin; Peng Xie; Ming-Yang Li; Yue Ren; Guang-Yan Sun (Chemical Engineering Journal, 2026)

Fe-N-C-supported LaFeO3 heterojunction electrodes for efficient copper and fluoride removal in symmetric capacitive deionization - Shaojian Xie; Yujia Wang; Rui Zhang; Lei Huang; Jia Yan; Zhenxin Chen; Hongguo Zhang; Meng Li; Hongbo Zeng (Water Research, 2026)

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

WaveCastNet-C: Forecasting the significant wave height in the China Sea with a fully convolutional neural network - Hao Dai; Zhihan Xie; Famei Lei; Xining Zhang; Guomei Wei; Rui Lin; Weijie Zhang; Shaoping Shang (Ocean Engineering, 2026)

Triple-synergistic nanotherapeutics for acute and chronic colitis management via programmable multidimensional modulation - Penghui Wang; Yue Zhao; Ning Tian; Xiangling Liu; Tenghui Tian; Difu Zhu; Fangbing Liu; Hengyan Liu; Ling Li; Zhiyu Ren; Deok Chun Yang; Lei Zhao; et al. (Chemical Engineering Journal, 2026)

Thermodynamic Analysis and Dynamic Evolution of Microscopic Physicochemical Properties During the Oxidation Process of Low-Rank Coal - Linhao Xie; Hongqing Zhu; Rui Li; Lei Zhang; Qi Yuan; Tianyu Li; Houwang Wang (Natural Resources Research, 2026)

Immobilization and magnetic removal of lead in contaminated soils using a waste-derived magnetic molecular sieve - Chang Lei; Xiu-Ru Xie; Lai-Shou Long; Rui Li; Zhi-Ping Fu; Zhi-Yue Zhao (Journal of Soils and Sediments, 2026)

Corrigendum to “Anodic microbiota reassembly via cell-cell interactions confers oxygen resilience in microbial fuel cells” [Bioresour. Technol. 443 (2026) 133815] - Jingtong Dai; Xinyu Cao; Heng Xu; Can Wang; Likai Hao; Binbin Xie; Shun Li; Kelei Zhao; Lei Cui; Zhao Yin; Baoshi Yao; Tao Chen; et al. (Bioresource Technology, 2026)

Anodic microbiota reassembly via cell-cell interactions confers oxygen resilience in microbial fuel cells - Jingtong Dai; Xinyu Cao; Heng Xu; Can Wang; Likai Hao; Binbin Xie; Shun Li; Kelei Zhao; Lei Cui; Zhao Yin; Baoshi Yao; Tao Chen; et al. (Bioresource Technology, 2026)

Correction: Lei et al. Transcriptomic Analysis of Non-Specific Immune Responses in the Rice Field Eel (Monopterus albus) Infected with Pallisentis (Neosentis) celatus. Fishes 2024, 9, 452 - Qin Lei; Xiaoling Li; Hao Wu; Yiwen Wan; Yukun Xie; Jinwei Gao; Wenwen Suo; Ming Zeng; Lingli Liu; Dongsheng Ou; Zhonggui Xie; Rui Song (Fishes, 2025)
In the original publication [...]

Time trend of urine metal levels in preschool children in the electronic waste recycling area and its association with hemoglobin levels - Rongyi Kang; Jieting Chen; Kaihui Li; Rui Sun; Jian Zhang; Chenxu Dai; Xijin Xu; Bo Xie; William W. Au; Lei Tan; Xia Huo (International Archives of Occupational and Environmental Health, 2025)

Tfh cell-mediated impairment of rotavirus-specific antibodies by PAH and PFAS co-exposure in seropositive children - Jian Zhang; Jieting Chen; Rongyi Kang; Chenxu Dai; Bo Xie; Kaihui Li; Rui Sun; Xiangbin Zheng; Lei Tan; Xijin Xu; Xia Huo (Journal of Hazardous Materials, 2025)

Molecular detection and phylogenetic analysis of lumpy skin disease virus in Yunnan Province, China from 2019 to 2023 - Jun Yao; Xue Li; Lei Tan; Lin Gao; Pei Zhu; Jiarui Xie; Rui Yan; Taoyin Yu; Fengyi Xia; Qiyun Chen; Bangquan Zeng; Jiaping Yang (Veterinary Research Communications, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Modulating band structure of MoO3 via W-doped for enhanced photo-induced charge transfer and SERS detection - Hongwen Cao; Yunpeng Cao; Jia He; Xin Xie; Zhijun Wang; Sen Sun; Rui Zhong; Lei Sun; Yihan Wang; Kun Zhang (Chemical Engineering Journal, 2025)

An oral recombinant human type 5 adenovirus vector vaccine encoding the S protein of Type I feline coronavirus effectively protection against FCoV challenge in cats - Gu-nan Deng; Chang-zhan Xie; Ke-lei Zhou; Chun-sai He; Yuan-Zhen Ma; A.-jia Ake; Rui Guo; Kai Li; Chen Peng; Bin Zhang (Veterinary Microbiology, 2025)

Microscopic understanding of the reaction path and gas production mechanism of key functional groups in coal: Combination of molecular dynamics, quantum chemistry and experimental research - Binrui Li; Hongqing Zhu; Lei Zhang; Rui Li; Linhao Xie; Erhui Zhang; Baolin Qu; Lintao Hu (Fuel, 2025)

Experimental and quantum chemical study of synergistic inhibitor based on physicochemical interaction in the prevention of coal spontaneous combustion - Hongqing Zhu; Jiashuo Wang; Rui Li; Linhao Xie; Lei Zhang; Erhui Zhang; Lintao Hu (Fuel, 2025)

Evolution of and mechanisms controlling water chemistry in the Beijiang River Basin over the past four decades - Zaizhi Yang; Tao Jiang; Zuobin Liang; Xinfeng Zhao; Kun Ren; Di Tian; Lei Gao; Qirui Wu; Shaoheng Li; Rui Li; Lichun Xie; Jianyao Chen (Journal of Geochemical Exploration, 2025)

Solid-state fermentation of distillers grains with Aspergillus pachycristatus for echinocandin B biosynthesis - Jiaxin Tang; Weibing Zhang; Jing Xu; Luyan Sun; Yaqi Dang; Haoyang Li; Liyan Yu; Jing Su; Ting Xue; Rui Guo; Jun Xie; Lei Wang (Bioresource Technology, 2025)

The sedimentological heterogeneities and responses to controlling factors in Toutunhe Formation of Xiayan Rise, Junggar Basin - Nai-xiang He; Xiang Li; Ya-jie Ding; Rui Qi; Gang Xu; Zi-jian Han; Chao Hou; Lei Xie (Applied Geophysics, 2025)

Multi-epitope vaccines Xlc and Ddc against Glaesserella parasuis infection in mice - Lu Dai; Jiajia Wan; Rui Zhang; Tingting Xie; Yizhen Jia; Zhichao Lu; Fuxian Zhang; Wenting Ke; Feng Liu; Liancheng Lei (Veterinary Microbiology, 2025)

Efficient isolated iron catalysts for selective arylamines synthesis using waste H2S as hydrogen source - Xinhui Liu; Rui Xie; Xiaohai Zheng; Lijuan Shen; Ganchang Lei; Lilong Jiang (Chemical Engineering Journal, 2025)

Transcriptomic Analysis of Non-Specific Immune Responses in the Rice Field Eel (Monopterus albus) Infected with Pallisentis (Neosentis) celatus - Qin Lei; Xiaoling Li; Hao Wu; Yiwen Wan; Yukun Xie; Jinwei Gao; Wenwen Suo; Ming Zeng; Lingli Liu; Dongsheng Ou; Zhonggui Xie; Rui Song (Fishes, 2024)
Parasitic infestations present significant threats to the physiological health and ecological stability of aquatic species, frequently compromising immune defenses and elevating mortality rates. This study was conducted to elucidate the non-specific immune responses induced by Pallisentis (Neosentis) celatus infection in Monopterus albus, with a focus on intestinal histopathology and transcriptome gene expression. A histopathological examination revealed minor alterations in intestinal villi under low-level infection. A transcriptome analysis, performed using Illumina sequencing technology, identified 347 upregulated and 298 downregulated genes involved in critical biological pathways, such as lipid metabolism, immune responses, and the regulation of inflammatory processes. GO and KEGG analyses indicated the upregulation of immune-related pathways, including the RIG-I-like and IL-17 signaling pathways, highlighting a robust intestinal immune response. Conversely, the complement pathway was found to be downregulated, with significant suppression of C9, suggesting that the parasite may engage in immune evasion. Fluorescein-labeled C9 antibody assays confirmed reduced complement C9 levels in the infected tissues. A real-time PCR analysis identified the differential expression of eight genes, including C5, maats1, CFI, and gmnc, which were consistent with the sequencing results. These findings suggest that Pallisentis (Neosentis) celatus infection compromises intestinal health, induces inflammation, and activates non-specific immune responses in Monopterus albus. However, Pallisentis (Neosentis) celatus appears to evade the host immune response by suppressing the activation of complement components, thereby facilitating its reproductive parasitism.

Probiotic nucleotides increase IL-10 expression in airway macrophages to mitigate airway allergy - Jinmei Xue; Zhizhen Liu; Bailing Xie; Rui Dong; Juan Wu; Yisha Wu; Zhihan Xu; Yuhe Tian; Yao Wei; Zhigang Geng; Lei Lu; Yu Liu; et al. (Inflammation Research, 2024)

24-epibrassinolide enhances drought tolerance in grapevine (Vitis vinifera L.) by regulating carbon and nitrogen metabolism - Guihua Zeng; Zhuowu Wan; Rui Xie; Bingyuan Lei; Chan Li; Feifei Gao; Zhenwen Zhang; Zhumei Xi (Plant Cell Reports, 2024)

Mongolian HCC vs. Caucasian HCC: The Metabolic Reprogramming Process in Mongolian HCC is an Interesting Difference - Rui Huang; Kun Yang; Zejuan Zhang; Lei Song; Kaizhong Dong; Xiaofeng Xie; Xiangjun Hai (Biochemical Genetics, 2024)

Deep learning in water protection of resources, environment, and ecology: achievement and challenges - Xiaohua Fu; Jie Jiang; Xie Wu; Lei Huang; Rui Han; Kun Li; Chang Liu; Kallol Roy; Jianyu Chen; Nesma Talaat Abbas Mahmoud; Zhenxing Wang (Environmental Science and Pollution Research, 2024)

Peripheral BDNF Regulates Somatosensory–Sympathetic Coupling in Brachial Plexus Avulsion-Induced Neuropathic Pain - Hang Xian; Huan Guo; Yuan-Ying Liu; Jian-Lei Zhang; Wen-Chao Hu; Ming-Jun Yu; Rui Zhao; Rou-Gang Xie; Hang Zhang; Rui Cong (Neuroscience Bulletin, 2023)

Low-dose IL-2 Treatment Rescues Cognitive Deficits by Repairing the Imbalance Between Treg and Th17 Cells at the Middle Alzheimer’s Disease Stage - Lin Yuan; Lei Xie; Hao Zhang; Yu Zhang; Yunbo Wei; Jinhong Feng; Li Cui; Rui Tian; Jia Feng; Di Yu; Cui Lv (Journal of Neuroimmune Pharmacology, 2023)

Development and validation a prognostic model based on natural killer T cells marker genes for predicting prognosis and characterizing immune status in glioblastoma through integrated analysis of single-cell and bulk RNA sequencing - Jiahe Hu; Lei Xu; Wenchao Fu; Yanan Sun; Nan Wang; Jiheng Zhang; Chengyun Yang; Xiaoling Zhang; Yuxin Zhou; Rongfang Wang; Haoxin Zhang; Ruishu Mou; et al. (Functional & Integrative Genomics, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Engineering triple internal electric fields in Ag NWs@BaTiO3 composites for ultrasonic-visible-light driven antibacterial activity - Guoqiang Shu; Yaqi Lin; Rui Zhong; Xiaofan Su; Shanhong Guo; Chao Wang; Changan Zhou; Lei Song; Li Xie; Kui Ma; Hairong Yue (Chemical Engineering Journal, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

Correction: Celecoxib and octreotide synergistically ameliorate portal hypertension via inhibition of angiogenesis in cirrhotic rats - Jin-Hang Gao; Shi-Lei Wen; Shi Feng; Wen-Juan Yang; Yao-Yao Lu; Huan Tong; Rui Liu; Shi-Hang Tang; Zhi-Yin Huang; Ying-Mei Tang; Jin-Hui Yang; Hui-Qi Xie; et al. (Angiogenesis, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Risk Evaluation of Navigation Environment Based on Dynamic Weight Model and Its Application - Shuzhe Chen; Lei Wu; Cheng Xie; Li Zhou; Rui Wang; Zhao Liu; Quanlong Zhu; Lianzhong Zhu (Journal of Marine Science and Engineering, 2022)
In order to scientifically and reasonably evaluate the safety risk of ship navigation, to and better solve the problems of the poor sensitivity of static evaluation and insufficient ability to grasp the overall dynamic situation, in this paper, representative safety evaluation indexes for ship navigation are screened and the initial weight of each index is confirmed in combination with the improved analytic hierarchy process (IAHP), in order to learn the changes of navigation environment and accident samples in the waters in the jurisdiction. Finally, the dynamic risk evaluation is carried out by constructing a dynamic weight evaluation model for the safety risk of the navigation environment based on the weight fusion of subjective and objective impact factors. The waters under the jurisdiction of Sanya, China were selected for the study, and the navigation risk of the waters in the jurisdiction was calculated by using the dynamic weight evaluation model based on navigation risk. The calculation results are highly consistent with the results based on the statistics of historical accidents and the analysis of the characteristics of the navigation environment in the jurisdiction. The navigation risk in this water area is the greatest from May to September every year. The dynamic weight evaluation model can not only overcome the subjective evaluation distortion in the traditional risk evaluation theory of navigation environment in practical applications, but can also provide a scientific theoretical basis for the dynamic evaluation and early warning of the risk of ship navigation environments through continuous sample learning.

Characteristics, Sources, and Risks of Polycyclic Aromatic Hydrocarbons in Topsoil and Surface Water from the Liuxi River Basin, South China - Zhenglan Xie; Lei Gao; Zuobing Liang; Jianyao Chen; Shaoheng Li; Aiping Zhu; Yu Wu; Zhigang Yang; Rui Li; Zhuowei Wang (Archives of Environmental Contamination and Toxicology, 2020)

Assessment of Metal Pollution, Its Potential Health Risks, and Origin in Different Land Use Types in Zhuhai City, China - Zuobing Liang; Lei Gao; Xinfeng Zhao; Jianyao Chen; Zhenglan Xie; Shaoheng Li; Rui Li; Zhigang Yang (Archives of Environmental Contamination and Toxicology, 2019)

Biglycan, a Nitric Oxide-Downregulated Proteoglycan, Prevents Nitric Oxide-Induced Neuronal Cell Apoptosis via Targeting Erk1/2 and p38 Signaling Pathways - Sujuan Chen; Dandan Guo; Wei Zhang; Yunfei Xie; Haijie Yang; Binfeng Cheng; Lei Wang; Rui Yang; Jiajia Bi; Zhiwei Feng (Journal of Molecular Neuroscience, 2018)

Celecoxib and octreotide synergistically ameliorate portal hypertension via inhibition of angiogenesis in cirrhotic rats - Jin-Hang Gao; Shi-Lei Wen; Shi Feng; Wen-Juan Yang; Yao-Yao Lu; Huan Tong; Rui Liu; Shi-Hang Tang; Zhi-Yin Huang; Ying-Mei Tang; Jin-Hui Yang; Hui-Qi Xie; et al. (Angiogenesis, 2016)
Abnormal angiogenesis is critical for portal hypertension in cirrhosis. Except for etiological treatment, no efficient medication or regime has been explored to treat the early stage of cirrhosis when angiogenesis is initiated or overwhelming. In this study, we explored an anti-angiogenesis effort through non-cytotoxic drugs octreotide and celecoxib to treat early stage of cirrhotic portal hypertension in an animal model. Peritoneal injection of thioacetamide (TAA) was employed to induce liver cirrhosis in rats. A combination treatment of celecoxib and octreotide was found to relieve liver fibrosis, portal venous pressure, micro-hepatic arterioportal fistulas, intrahepatic and splanchnic angiogenesis. Celecoxib and octreotide exerted their anti-angiogenesis effect via an axis of cyclooxygenase-2/prostaglandin E2/EP-2/somatostatin receptor-2, which consequently down-regulated phosphorylation of extracellular signal-regulated kinase (p-ERK)–hypoxia-inducible factor-1α (HIF-1α)–vascular endothelial growth factor (VEGF) integrated signaling pathways. In conclusions, combination of celecoxib and octreotide synergistically ameliorated liver fibrosis and portal hypertension of the cirrhotic rats induced by TAA via the inhibition of intrahepatic and extrahepatic angiogenesis. The potential mechanisms behind the regimen may due to the inactivation of p-ERK–HIF-1α–VEGF signaling pathway.

Integrated SWAT model and statistical downscaling for estimating streamflow response to climate change in the Lake Dianchi watershed, China - Jing Zhou; Dan He; Yufeng Xie; Yong Liu; Yonghui Yang; Hu Sheng; Huaicheng Guo; Lei Zhao; Rui Zou (Stochastic Environmental Research and Risk Assessment, 2015)

Two new compounds from a marine-derived fungus Penicillium oxalicum - Pei-Le Wang; Dan-Yi Li; Lei-Rui Xie; Xin Wu; Hui-Ming Hua; Zhan-Lin Li (Natural Product Research, 2014)

Y chromosome diversity and paternal origin of Chinese cattle - Ran Li; Wen-Mei Xie; Zhen-Hua Chang; Shao-Qiang Wang; Rui-Hua Dang; Xian-Yong Lan; Hong Chen; Chu-Zhao Lei (Molecular Biology Reports, 2013)

A new cyclonerol derivative from a marine-derived fungus Ascotricha sp. ZJ-M-5 - Lei-Rui Xie; Dan-Yi Li; Zhan-Lin Li; Hui-Ming Hua; Pei-Le Wang; Xin Wu (Natural Product Research, 2013)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)